Práticas de cura: saberes de africanos e afro-brasileiros em Desterro (SC) na segunda metade do século XIX - Souza, Adriana Maria de (2017)
The objective of this research is to understand how the population composed of Africans and Afros Brazilians in Desterro (SC), especially the women, healers, mourners and healers who used the ancestral knowledge, for the practices of healing between 1844 and 1889 in Desterro (SC). This period, when posture codes, the terms of well-being in communion with the hygienist's medical gaze, and the desire to modernize by local political elites were in vogue, with the intention of controlling the poor populations and, consequently, the called healing practices developed by populations of African origin. The empire and the beginning of the Republic, with their ideals of modernization, hygiene and the fight against insalubrity, based on the absolute knowledge of medicine, also tried to regulate the practices called "witchcraft." The numerous works that approach the theme of healers and healers in Santa Catarina, with few exceptions, mainly focus on white women who are believed to be Azorean descendants. The African presence and its healing practices related to patient care appear in the background. We used as main source of research, announcements of local newspapers, inventory, trades and correspondence exchanged between the administration of the province of Santa Catarina and the empire, linked to the practices of healing and prayers on the island of Santa Catarina